2014
DOI: 10.1080/0144235x.2014.911548
|View full text |Cite
|
Sign up to set email alerts
|

Chirality effects in gas-phase spectroscopy and photophysics of molecular and ionic complexes: contribution of low and room temperature studies

Abstract: This review focuses on chirality effects in spectroscopy and photophysics of chiral molecules or protonated ions, and their weakly bound complexes, isolated in the gas phase. Low-temperature studies in jet-cooled conditions allow disentangling the different interactions at play and shed light on the ancillary interactions responsible for chiral recognition, like OH…π or CH…π, which would be blurred at room temperature. The consequences of these interactions on chiral recognition in condensed phase are describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 311 publications
(401 reference statements)
0
47
0
Order By: Relevance
“…9 The present results and the formerly reported characterization of the in the ion trap may be a reflection of kinetic trapping of the primarily formed species from the reaction between cisplatin and 5'-dAMP. 49,56,57 In a further effort to gain an insight into the process occurring in solution, we have performed additional calculations taking solvation into account through the use of the polarized continuum model (PCM). The results are reported in the Supporting Information (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…9 The present results and the formerly reported characterization of the in the ion trap may be a reflection of kinetic trapping of the primarily formed species from the reaction between cisplatin and 5'-dAMP. 49,56,57 In a further effort to gain an insight into the process occurring in solution, we have performed additional calculations taking solvation into account through the use of the polarized continuum model (PCM). The results are reported in the Supporting Information (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, severala uthors have reported that, in av ariety of instances, the ion population sampled by ESI reflects kinetic trapping rather than being governed by the gas-phase thermodynamics. [39][40][41] The increased relative stabilityo fN t relative to N p isomers when solvation is accountedf or lends further support to this line of reasoning, [42] althought hermodynamic considerations alone do not provide au niform rationale to the reactivity patterns observed in the solution chemistry of platinum(II) complexes. [10] This study,w hich sheds light on the early step of the cisplatin reaction with histidine andh istidine-containing peptides and proteins,p aves the way towards at horough appraisal of the cisplatin interaction with amino acid targets at the molecular level.…”
Section: Resultsmentioning
confidence: 99%
“…The observation of a higher fragmentation efficiency for the heterochiral complex, despite it being calculated to be slightly more stable than the homochiral system, was explained by the presence of a second, lower‐energy, conformer of the homochiral complex. The chiral effects of molecular and ionic complexes have been widely studied with different theoretical and experimental approaches in gas‐phase spectroscopy …”
Section: Introductionmentioning
confidence: 99%
“…The chiral effects of molecular and ionic complexes have been widely studied with different theoretical and experimental approaches in gas-phase spectroscopy. 13 The previous chiral recognition experiments were performed in ion trap configurations, with numerous collisions with a target gas over a distribution of kinetic energies. We recently embarked on a program using ion beams and thin targets in order to study chiral interactions in single, [This article is part of the Special Issue: Proceedings of 28th International Symposium on Molecular Chirality, Heidelberg 2016.…”
Section: Introductionmentioning
confidence: 99%